2020
DOI: 10.3390/nano10091895
|View full text |Cite
|
Sign up to set email alerts
|

Metal Organic Framework Derived MnO2-Carbon Nanotubes for Efficient Oxygen Reduction Reaction and Arsenic Removal from Contaminated Water

Abstract: Even though manganese oxides are attractive materials for batteries, super-capacitors and electro-catalysts for oxygen reduction reactions, in most practical applications MnO2 needs to be hybridized with conductive carbon nano-structures to overcome its inherent poor electrical conductivity. In this manuscript we report microwave-assisted synthesis of MnO2 embedded carbon nanotubes (MnO2@CNT) from Mn-H3BTC (benzene-1,3,5-carboxylic acid) metal organic frameworks (MOF) precursors. Using graphene oxide as microw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Ni doping enhances the conductivity of MnO 2 and increases the surface area and cycle stability of the composite. Microwave irradiation heating reduces energy consumption compared to hydrothermal reactions, effectively shortens the synthesis time of complexes, and improves product homogeneity [ 110 , 111 , 112 ]. For example, Sivaraj et al [ 110 ] reported a microwave-assisted process to synthesize the hybrid CNTs-MnO 2 nanocomposite.…”
Section: Preparation Methods Of Mno 2 -Carbon Comp...mentioning
confidence: 99%
“…Ni doping enhances the conductivity of MnO 2 and increases the surface area and cycle stability of the composite. Microwave irradiation heating reduces energy consumption compared to hydrothermal reactions, effectively shortens the synthesis time of complexes, and improves product homogeneity [ 110 , 111 , 112 ]. For example, Sivaraj et al [ 110 ] reported a microwave-assisted process to synthesize the hybrid CNTs-MnO 2 nanocomposite.…”
Section: Preparation Methods Of Mno 2 -Carbon Comp...mentioning
confidence: 99%
“…This powder was subsequently transferred into a glass vial and subjected to microwave radiation for 45 s at 700 W to yield a fluffy powdery solid of nitrogen-doped carbon nanotubes anchored on reduced graphene oxide (MDNCNT@rGO). Details of electrode preparation and characterization are provided in supplementary file, whereas EMI testing was carried out as per the protocol reported in our previous paper [42].…”
Section: Experimental Synthesis Of 3dcns From Mof Precursorsmentioning
confidence: 99%
“…15,16 Despite signicant advances in the development of aqueous ZMBs, there are still some obstacles preventing their commercial application. To date, four typical materials have been widely reported for zinc ion storage, Prussian blue analogues, [17][18][19] manganese-based complexes, [20][21][22] V-based complexes, [23][24][25] and organic compounds. 10 Among the widely used inorganic cathodes, vanadium-based materials have attracted conspicuous attention due to their high specic capacity and stable coulombic efficiency.…”
Section: Introductionmentioning
confidence: 99%